(untitled) (International Journal of Physiology, 2020)
Background: Occurrence of menarche at the earlier age has been attributed to a significant number of adverse health outcomes. Depression, eating disorders, metabolic syndrome and Type II diabetes mellitus have been identified as the major adverse health related issues. Furthermore in relation to early age of menarche has been identified as a risk factor for breast and endometrial cancer due to the increased exposure to estrogen. Hence, it is important to give awareness in adopting healthy eating habits and involving in daily physical exercise. Aim: To measure the body mass index in adolescent girls and correlate between the age of menarche and body mass index in adolescent girls. Methodology: This is cross-sectional study with a sample size of 200 female students between the age group of 17 – 19 years attending different courses (MBBS, BDS, AHS and BPT) in Melmaruvathur Adhiparasakthi Institute of Medical Sciences and Research, Melmaruvathur. An informed consent will be obtained from the participants. A dietary history will be taken by questionnaire. The anthropometric measurements for calculating the BMI will be measured using calibrated instruments. Result: The results of this study the statistically significant were seen among the age of menarche and the BMI, pearson chi-square is 21.876 and p value is 0.009 and also statistical significant was seen when compared regularity of periods with BMI, pearson chi-square is 10.018 and p value is 0.01. There was no statistical significant when compared waist-hip ratio with age of menarche and regularity of periods. Conclusion: The age of menarche had a tight connection with BMI. Increase in BMI causes early age of menarche. So having increased body fat, increased body weight, high intake of protein, high-calories foods and sedentary life style causes early age of menarche in young healthy girls.